EFEK PEMBERIAN OBAT ANESTESI INHALASI SEVOFLURAN TERHADAP PERUBAHAN FREKUENSI NADI INTRA ANESTESI DI KAMAR OPERASI RUMAH SAKIT UMUM DAERAH UMBU RARA MEHA WAIGAPU - EMANUEL ILEATAN LEWAR (JURNAL INFO KESEHATAN, 2015)
Background: Anaesthesia represents the important shares in surgery action. Anesthesia consisted of by some types, wrong of anesthesia inhalation which in this time have a lot of wore. Its drug all kinds of, worn at this research is sevoflurane. To take care of the security and patient safety, during gift of anesthesia of patient circumstance need in monitoring. The matter which needs in monitoring changes hemodynamic one of them is that is a change of frequency Nadi. Hence from that this research aims to know the gift effect medicine the anesthesia sevoflurane to frequency Nadi. Method: This Research represents analytic of observational use the approach of cross-sectional. Sample taken by purposive is the sampling of a patient using anesthesia of inhalation sevoflurane after sample fulfills the criterion of inclusion and ekklesia. At this research take 25 subjects and analyzed to use the independent test. Result of research: From research data, got by the result of value p of an independent unit, assess the p of at phase of frequency Nadi of early, phase induce and phase intubasi is 0,04; 0,00; 0,02, for the phase of insisting of at minute 5, minute of 10 and minute 5 is 0,02; 0,0; 0,03. This result indicates that the value p < 0,05 were the result significant or there are difference having a meaning of statistically. Conclude the research: anesthesia of Inhalasi sevoflurane give the influence to change of frequency Nadi and good and also stabilize the frequency Nadi in its use during surgery.